Factors influencing the transferability of occupational safety and health economic incentive schemes between different countries - Elsler, Dietmar; Eeckelaert, Lieven (Scandinavian Journal of Work, Environment & Health, 2010)
' ' OBJECTIVES ': 'This article looks at the factors that influence the transferability of different types of occupational safety and health (OSH) economic incentives from one country to another. ' ' METHODS ': 'To review the legal, political, and cultural framework conditions for economic incentive schemes in the European Union (EU), the European Agency for Safety and Health at Work (EU-OSHA) surveyed EU member states about the state of such schemes in their countries. In addition to the survey responses, relevant information on existing schemes and their national context within the 27 EU member states was gathered through reports, articles, and databases. Following this, countries were clustered according to cross-cultural differences. ' ' RESULTS ': 'Despite the apparent variations in Europe’s social security systems, there is a high degree of similarity between the countries regarding the basic criteria of design of the system. In addition, different kinds of incentives are used in different member states regardless of the social insurance system. When it comes to insurance incentive schemes, the fundamental difference between countries is whether the workers’ compensation scheme is based on a competitive market between private insurance companies or a kind of monopoly structure, where the employers do not have the choice between several insurance companies. A clear majority of 19 of the 27 EU member states have a monopoly system. ' ' CONCLUSIONS ': 'Subsidy systems, tax incentives, and insurance-based “experience rating” are theoretically possible in all EU countries. In competitive insurance markets, effort-based incentives are more difficult to achieve. A possible solution could be the introduction of long-term contracts or the creation of a common prevention fund, financed equally by all insurers.
Keywords: cross-cultural differences; discussion paper; economic incentive; economic incentive scheme; economics; external economic incentive; occupational safety and health; OSH